(untitled) (Academia Journal of Medicine, 2024)
Present in-vitro research conducted to find out the frequency of second mesiobuccal canals in permanent maxillary molars. Eighty extracted, intact maxillary permanent molars were selected for the present study. Following that, a slow-speed diamond disc was used to divide the occlusal sections of the crowns at the cement enamel junction. Using a safe-end diamond bur, overhanging dentin that covered the canal orifices was removed to allow straight line visibility. Under an x8 magnification, the teeth were photographed from their occlusal side. Result showed that the first and second maxillary molars, MB2 canals were found in 70% and 55%, respectively. In conclusion it is crucial during endodontic procedures on maxillary molars to cautiously check pulpal floor to detect any "extra" canals, notably the second mesiobuccal canal, by scraping away the constrictive dentin above the orifices.